Surgical fixation of posterior cruciate ligament avulsion fracture from tibial attachment using cannulated cancellous screw: a clinical, radiological and functional outcome evaluation - Mondal, Aniruddha; Das, Ayon (International Journal of Research in Orthopaedics, 2021)
Background: PCL (posterior cruciate ligament) is the main posterior stabilizer of the knee and plays a role in central axis controlling and imparting rotational stability to the knee. Injury to PCL presents commonly with avulsion fractures from its tibial attachment. An avulsion fracture of the PCL, if not surgically fixed, may lead to secondary changes in the knee joint. The aim of the study was to evaluate the clinical and functional results in patients with PCL tibial avulsion fractures treated by CC (cannulated cancellous) screw fixation. Methods: This was a prospective study conducted at a tertiary care government hospital in Kolkata, between December 2018 to July 2020 on patients who underwent CC screw fixation for post-traumatic PCL avulsion fracture from tibial site. All patients were followed up for 9 months. Lysholm knee score was used to assess the functional outcomes of the patients. Results: In a total of 10 patients, 9 (90%) patients showed excellent and 1 (10%) patient had good result during the final follow-up. 80% patients did not develop any complications. At the end of 9 months, the mean Lysholm score was 95.6. 8 (80%) patients achieved almost full knee ROM post-operatively by the end of final follow-up. Conclusions: Surgical fixation using CC screws is a simple, easy, safe and reproducible method without requiring significant expertise for achieving good stability in PCL tibial site avulsion fractures, where early intervention prevents significant late disability as it provides an excellent clinical, functional and radiographic outcome along with good joint function.